ANALISIS YURIDIS MALPRAKTIK MEDIS DALAM PERSPEKTIF HUKUM KESEHATAN DAN PERLINDUNGAN PASIEN DI INDONESIA - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (CV. ADIBA AISHA AMIRA, 2026)
Cases of alleged medical malpractice in Indonesia have shown a significant upward trend, with 51 complaints of professional disciplinary breaches between 2023 and 2025 and 24 cases resulting in patient deaths. This study aims to analyse medical malpractice from a legal perspective, focusing on health law and patient protection in Indonesia. The research method employs a normative legal approach with a conceptual legislative framework. The findings indicate that medical malpractice constitutes a complex legal offence involving three dimensions—civil, criminal and administrative law—with negligence, medical procedural errors and breaches of professional standards as key elements. Law No. 17 of 2023 on Health, through Articles 440 and 447, introduces a new, more specific framework for criminal liability applicable to healthcare professionals and hospitals based on the doctrine of vicarious liability. Legal protection for patients who are victims of malpractice is still not functioning optimally, even though patients’ rights are guaranteed in law, due to the heavy burden of proof, limited access to medical records, and administrative sanctions that lack a deterrent effect. This study concludes that there is a need for health law reform to strengthen patients’ access to justice, clarify the responsibilities of healthcare professionals, and reinforce professional oversight mechanisms so that the principle of substantive justice is truly realised.